Fluorescent Determination of Mercury(II) and Glutathione with Binding to Thymine–Guanine Base Pairs. (13th April 2023) - Zhang, Liyuan; Liu, Jinxiao; Gao, Mengying; Han, Li; Liu, Xueguo; Xing, Xiaojing
Abstract: It has been demonstrated that thymine–guanine (T–G) mismatches in duplex DNA specifically coordinate with mercury ion (Hg 2+ ), forming T–Hg 2+ –G base pairs. However, the binding performance of T–G mismatches with Hg 2+ and its application in biosensors have been rarely reported so far. In this study, the binding between T–G mismatches and Hg 2+ was investigated and efforts were made to systematical characterize the analytical performance of T–G mismatches in the determination of Hg 2+ and glutathione (GSH), where the thymine–thymine (T–T) mismatches were used as the reference. In specific, Hg 2+ induced the conformational change of the fluorescently labeled DNA (FDNA) consisted of seven T–T mismatches, resulting in the dissociation of FDNA with its complementary sequence labeled with a quencher, followed by the disappearance of the fluorescence resonance energy transfer (FRET). The experimental results suggest that the T–G mismatch showed faster signaling kinetics and high sensitivity in sensing Hg 2+ with a limit of detection of 4.72 nM for Hg 2+ . Moreover, the platform based on the T–Hg 2+ –G structure was successfully applied to determine glutathione with a detection limit of 18.96 nM. These findings of this study may describe the interactions between Hg 2+ and nucleobases and extend the applications of Hg 2+ –mediated base pairs.